Karakteristik Keselamatan Lalu Lintas Di Kota Manado - Syaban, Alfath Satria Negara; M. Akbar Fauzan; Dede F. Fadhilla (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
There has been a significant increase in transportation facilities in the city of Manado which has affected the level of traffic congestion to date and has resulted in very high social costs. Indirectly it affects the increase in traffic problems, one of which is traffic accidents. The purpose of this research is to find appropriate alternative solutions for the community to reduce accidents and make efforts to increase traffic safety in the city of Manado. This research was made using an exploratory quantitative research methodology with a triangulation model that examines phenomena based on the interpretation of descriptive statistical data, observation as well as documentation and field surveys. The results of the analysis show that there are 6 accident-prone road sections in Manado City, namely Jalan AA Maramis, Jalan Ring Road I, Jalan Sam Ratulangi, Jalan RW Monginsidi, Jalan Piere Tendean, and Jalan RE Martadinata. Adequate street light facilities are needed and there is a need to improve the lights so that they are not covered by vegetation on several roads, especially roads which are prone to accidents.